Peran Unit Kegiatan Kemahasiswaan (UKM) Dalam Percepatan Masa Tunggu Lulusan (Suatu Studi Kasus Pada AKBID Delima Persada Gresik) - Ariestiningsih, Eka Srirahayu (FIRM Journal of Management Studies, 2018)
Granting an independent midwife, is part of the vision phrase that will be realized by the Academy ofMidwifery (AKBID) Delima Persada Gresik. To realize that vision of the AKBID Delima PersadaGresik, is obliged to give knowledge to students as learners to have entrepreneur spirit. As the effectthe enactment of the Regulation of the Midwife Professional Organization, the Ikatan Bidan Indonesia(IBI), that to establish an Independent Midwife Practice Clinik / Klinik Bidan Praktek Mandiri(BPM), must have an internship certificate for 2 (two) years. it is considered burdensome for somegraduates waiting for 2 (two) years to be able to open the Clinic of Independent Practice Midwife/Klinik Bidan Praktek Mandiri (BPM) therefore are some graduates working out of their skills asmidwife , as well as many graduates of Midwife who implements activities gained form StudentActivity Unit/Unit Kegiatan Mahasiswa (UKM) of Entrepreneurship to open business independentlywhile applying internship at Senior Midwife. This research as a follow-up research that has been donein the Academy of Midwifery Delima Persada Gresik at 2017. The result of the research that has beendone is Student Activity Unit/Unit Kegiatan Mahasiswa (UKM) entreprenurship has been providingknoledge of haw to make porridge as an additional food /Makanan Tambahan (MT) ASI, organic milkporridge for baby and child under five years (Balita), and service product baby massage and baby spa.Knowledge and skill provided Entrepreneurship?s UKM expected to be a provision to open theopportunity to build an independent business that will accelerate the waiting period to get a job. Inthis research, the author wan to know whether Entrepreneurship?s UKM really have a role inaccelerating the waiting period of graduates Academy of Midwifery (AKBID) Delima Persada Gresik.Research Method used is qualitative method, and Object of research these are graduates of AKBIDDelima Perada Gresik.